Characterization of the malaria parasite optical features for development of a non-invasive diagnostic device - Baptista, Vitória Cunha (2019)
[Excerpt] Early and accurate malaria diagnosis is critical for the disease control and elimination [1]. Microscopy and/or immuno-rapid tests remain the standard diagnosis [2, 3], nevertheless it requires a skin puncture for blood sampling and not sensitive enough for reliable detect lowdensity parasitemias, urging the need to develop more sensitive and non-invasive tools. Symptoms of the disease starts when parasites infect the red blood cell (RBC), suffering biochemical and morphological changes [4]. Parasite survival is dependent on hemozoin (Hz) formation as a by-product of heme detoxification process of the parasite upon haemoglobin (Hb) degradation and therefore a good unique feature to identify parasites presence in patients’. Taking advantage of the fact that the Hz and Hb molar extinction coefficients differ significantly, especially at certain wavelengths [4, 5], and their proportion is inversely related upon parasite maturation inside the RBC, each stage of malaria is characterized by specific absorbance and reflectance spectra, according to the Hb/Hz concentrations on the iRBC. [...]